Best practices for the development and fit-for-purpose validation of biomarker methods: a conference report - Joel Mathews; Lakshmi Amaravadi; Steven Eck; Lauren Stevenson; Yow-Ming C. Wang; Viswanath Devanarayan; John Allinson; Kelly Lundsten; Michele Gunsior; Yan G. Ni; Marc-Olivier Pepin; Audrey Gagnon; et al. (SpringerOpen, 2022)
Abstract This conference report summarized a full-day workshop, "best practices for the development and fit-for-purpose validation of biomarker methods," which was held prior to the American Association of Pharmaceutical Scientists (AAPS) PharmSci360 Congress, San Antonio, TX, November 2019. The purpose of the workshop was to bring together thought leaders in biomarker assay development in order to identify which assay parameters and key statistical measures need to be considered when developing a biomarker assay. A diverse group of more than 40 scientists participated in the workshop. The workshop and subsequent working dinner stimulated robust discussion. While a consensus on best practices was not achieved, some common themes and major points to consider for biomarker assay development have been identified and agreed on. The focus of this conference report is to summarize the presentations and discussions which occurred at the workshop. Biomarker assay validation is a complex and an evolving area with discussions ongoing.